How to build a regional university: a case study that addresses policy settings, academic excellence, innovation system impact and regional relevance - Wise, Graham (2018)
A public university was established in 2014 as a cornerstone of Ecuador’s sweeping higher education reforms. Four years later, Universidad Regional Amazónica Ikiam had developed internationally benchmarked teaching, research and community service missions within the Ecuadorian Amazon. The creation of Ikiam occurred during a period of broad international discourse on the importance to universities of academic excellence, innovation system impact, and regional relevance. This case study tests whether a top-down state-driven development model can establish a university on principles of excellence, impact and relevance. The creation of Ikiam is analysed qualitatively and the results are discussed in context with national and international policy settings for higher education and innovation. This study provides insights for low and middle-income countries to strengthen higher education and innovation systems through university creation. Internationally it provides practical insights for university master planning taskforces to build organisational strength and distinctiveness through excellence, impact and relevance.